2018
DOI: 10.1155/2018/5324517
|View full text |Cite
|
Sign up to set email alerts
|

Parameters Influencing PET Imaging Features: A Phantom Study with Irregular and Heterogeneous Synthetic Lesions

Abstract: Aim To evaluate reproducibility and stability of radiomic features as effects of the use of different volume segmentation methods and reconstruction settings. The potential of radiomics in really capturing the presence of heterogeneous tumor uptake and irregular shape was also investigated. Materials and Methods An anthropomorphic phantom miming real clinical situations including synthetic lesions with irregular shape and nonuniform radiotracer uptake was used. 18F-FDG PET/CT measurements of the phantom were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 35 publications
2
37
0
Order By: Relevance
“…Concerns of reproducibility and reliability have been investigated by several studies with emphasis being put, respectively, on the impact onto PET radiomics features due to factors including PET scanner manufactures, acquisition and reconstruction algorithms, intensity discretization scheme, etc. [11][12][13][14] . As for the variability of contouring volume of interest (VOI) for inclusion to radiomics analysis, only a few existing studies investigated its impact on PET radiomics parameters 15,16 , even though contouring variability is commonly recognized as the largest source of error in the RT planning process 17 .…”
mentioning
confidence: 99%
“…Concerns of reproducibility and reliability have been investigated by several studies with emphasis being put, respectively, on the impact onto PET radiomics features due to factors including PET scanner manufactures, acquisition and reconstruction algorithms, intensity discretization scheme, etc. [11][12][13][14] . As for the variability of contouring volume of interest (VOI) for inclusion to radiomics analysis, only a few existing studies investigated its impact on PET radiomics parameters 15,16 , even though contouring variability is commonly recognized as the largest source of error in the RT planning process 17 .…”
mentioning
confidence: 99%
“…Recent results from Yan et al 26 and Veld et al 27 further confirmed this finding. Recently, Gallivanone et al 28 found that reconstruction settings largely affects the stability of radiomic features, and only 26% were stable when different parameters were considered in this anthropomorphic phantom study. Respiratory motion is another factor that should be concerned.…”
Section: Development Of Methodology and Technology In Radiomicsmentioning
confidence: 67%
“…In a recent study, lesions from oncological patients were segmented and 3D printed as shell compartments, which were filled with [18F]FDG radioactive gels . Plastic filaments of 3 mm diameter (Renkforce PLA300 Plastic PLA 3 mm) were used to imprint the compartments.…”
Section: Pet and Pet/ct Imaging Phantomsmentioning
confidence: 99%
“…(b) Positron emission tomography images of three simulated heterogeneous lesions. Copyright © 2018 Francesca Gallivanone et al [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Pet and Pet/ct Imaging Phantomsmentioning
confidence: 99%